Utilization of YouTube Media to Increase Student Motivation and Learning Outcomes in Network Systems Administration Subjects: Pemanfataan Media Yotube Untuk Peningkatan Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran Administrasi Sistem Jaringan - Sudarmadi, Ibnu (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2023)
Youtube as one of the video sharing sites has various features that support it to be used as an interesting learning media, researchers will conduct PTK related to how much benefit this site will have if it is used as a learning medium in class XI TKJ1 SMKN 7 Sijunjung in the first semester of the 2022/2023 academic year. This research consists of 2 cycles, each cycle consisting of planning, implementing actions, observation, and reflection. Implementation of actions using internet media and using other Information Technology equipment with uploading methods. The results showed that at the end of the first and second cycles the average activity and learning outcomes of students increased continuously from one meeting to the next, These results show that student activities and learning outcomes can be improved by utilizing Youtube media, which means this media can be applied so that students can develop their respective competencies.